0790 Racial Differences in Self-Efficacy for Positive Airway Pressure Therapy Among Individuals Newly Diagnosed with Obstructive Sleep Apnea. (25th May 2022) - Byrne, Sean; Sharma, Akanksha; Deng, Annan; Chu, Jen-Hwa; Sands, Scott; Wellman, Andrew; Redeker, Nancy; Yaggi, Henry; Zinchuk, Andrey
Abstract: Introduction: Continuous positive airway pressure (CPAP) therapy is the first-line treatment for OSA, yet its effectiveness is limited by poor adherence. Self-efficacy is an individual's belief that they can successfully execute a behavior to achieve a desired outcome. Evidence shows that self-efficacy predicts adherence to and outcomes of CPAP therapy, as do race and ethnicity. Little, however, is known about how self-efficacy may differ between racial and ethnic groups. Accordingly, we aimed to determine whether self-efficacy for CPAP differs by race and ethnicity among individuals newly diagnosed with OSA. Methods: Adults newly diagnosed with OSA and prescribed CPAP who were enrolled in the NICEPAP Study (n=267, NCT05067088), a prospective, observational cohort study investigating predictors of CPAP adherence were assessed. Those with need for non-CPAP therapy or with unstable medical conditions (e.g., cancer receiving chemotherapy, severe lung, heart or mental health disorders) were excluded. Exposures were race and ethnicity. Outcomes were subscale scores of the Self-Efficacy Measure for Sleep Apnea (SEMSA) completed prior to CPAP initiation: perceived risk, outcome expectancy, and self-efficacy. SEMSA sub-scale scores for race/ethnicity were compared using Kruskal-Wallis test. Medians (Q1, Q3) are reported. Results: We analyzed data for 52 participants (33 women) enrolled to date who identified as White (n=29), Black (n=14), More than one race (n=5) and Other (N=5). Participants were 51.0 (36.8, 58.8) years old with an apnea-hypopnea index of 17.0/hour (11.1, 26.0) and body-mass-index of 35.0 (31.6, 43.5) kg/m2. Baseline characteristics did not differ by race, except higher poverty (p=0.005) and less completed years of education (p=0.010) for Black participants. The SEMSA scores were not statistically different between each race. However, self-efficacy was significantly lower for Black participants vs. rest of the cohort combined (2.4 (1.9, 3.1) vs. 3.3 (2.7, 3.8) p=0.020). Poverty, but not education, may be a potential mediator of this relationship (mediation analysis p=0.052). There were no differences in SEMSA scores between Hispanic and Non-Hispanic participants. Conclusion: In our cohort, self-efficacy for OSA therapy was lower for Black participants compared to those of other races. Targeting early interventions to improve CPAP self-efficacy in Black patients may improve OSA therapy outcomes. Support (If Any):